Optimal. Leaf size=28 \[ 2+\left (e^3-\frac {1}{3 x}\right )^2+x-\log \left (x-x^2+\log (x)\right ) \]
________________________________________________________________________________________
Rubi [A] time = 0.57, antiderivative size = 31, normalized size of antiderivative = 1.11, number of steps used = 7, number of rules used = 5, integrand size = 76, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.066, Rules used = {6741, 12, 6742, 14, 6684} \begin {gather*} \frac {1}{9 x^2}-\log \left (-x^2+x+\log (x)\right )+x-\frac {2 e^3}{3 x} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 12
Rule 14
Rule 6684
Rule 6741
Rule 6742
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \frac {-2 x-7 x^2-9 x^3+27 x^4-9 x^5+e^3 \left (6 x^2-6 x^3\right )+\left (-2+6 e^3 x+9 x^3\right ) \log (x)}{9 x^3 \left (x-x^2+\log (x)\right )} \, dx\\ &=\frac {1}{9} \int \frac {-2 x-7 x^2-9 x^3+27 x^4-9 x^5+e^3 \left (6 x^2-6 x^3\right )+\left (-2+6 e^3 x+9 x^3\right ) \log (x)}{x^3 \left (x-x^2+\log (x)\right )} \, dx\\ &=\frac {1}{9} \int \left (\frac {-2+6 e^3 x+9 x^3}{x^3}-\frac {9 \left (-1-x+2 x^2\right )}{x \left (-x+x^2-\log (x)\right )}\right ) \, dx\\ &=\frac {1}{9} \int \frac {-2+6 e^3 x+9 x^3}{x^3} \, dx-\int \frac {-1-x+2 x^2}{x \left (-x+x^2-\log (x)\right )} \, dx\\ &=-\log \left (x-x^2+\log (x)\right )+\frac {1}{9} \int \left (9-\frac {2}{x^3}+\frac {6 e^3}{x^2}\right ) \, dx\\ &=\frac {1}{9 x^2}-\frac {2 e^3}{3 x}+x-\log \left (x-x^2+\log (x)\right )\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.18, size = 33, normalized size = 1.18 \begin {gather*} \frac {1}{9} \left (\frac {1}{x^2}-\frac {6 e^3}{x}+9 x-9 \log \left (-x+x^2-\log (x)\right )\right ) \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.58, size = 32, normalized size = 1.14 \begin {gather*} \frac {9 \, x^{3} - 9 \, x^{2} \log \left (-x^{2} + x + \log \relax (x)\right ) - 6 \, x e^{3} + 1}{9 \, x^{2}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.34, size = 34, normalized size = 1.21 \begin {gather*} \frac {9 \, x^{3} - 9 \, x^{2} \log \left (x^{2} - x - \log \relax (x)\right ) - 6 \, x e^{3} + 1}{9 \, x^{2}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.05, size = 30, normalized size = 1.07
method | result | size |
norman | \(\frac {\frac {1}{9}+x^{3}-\frac {2 x \,{\mathrm e}^{3}}{3}}{x^{2}}-\ln \left (x^{2}-x -\ln \relax (x )\right )\) | \(30\) |
risch | \(-\frac {-9 x^{3}+6 x \,{\mathrm e}^{3}-1}{9 x^{2}}-\ln \left (\ln \relax (x )+x -x^{2}\right )\) | \(31\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.41, size = 30, normalized size = 1.07 \begin {gather*} \frac {9 \, x^{3} - 6 \, x e^{3} + 1}{9 \, x^{2}} - \log \left (-x^{2} + x + \log \relax (x)\right ) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [F] time = 0.00, size = -1, normalized size = -0.04 \begin {gather*} \int -\frac {2\,x-\ln \relax (x)\,\left (9\,x^3+6\,{\mathrm {e}}^3\,x-2\right )-{\mathrm {e}}^3\,\left (6\,x^2-6\,x^3\right )+7\,x^2+9\,x^3-27\,x^4+9\,x^5}{9\,x^3\,\ln \relax (x)+9\,x^4-9\,x^5} \,d x \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.20, size = 24, normalized size = 0.86 \begin {gather*} x - \log {\left (- x^{2} + x + \log {\relax (x )} \right )} + \frac {- 6 x e^{3} + 1}{9 x^{2}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________